Agama, Pendidikan dan Tantangan Pemberantasan Korupsi di Indonesia - Tarsih, Entar (Tsamratul Fikri | Jurnal Studi Islam, 2020)
This article seeks to elaborate on the contribution of education in fighting corruption in Indonesia. By using the literature study method, this study found that the problem of corruption can be minimized through education because education is a human need. The concept of anti-corruption education is all efforts to reduce and eradicate corrupt behavior through programs in learning to provide awareness to individuals about the causes and consequences of corrupt behavior and encourage future generations to develop a firm resistance to any form of corruption. Learning programs that contain anti-corruption values are carried out in a meaningful manner so that they will remain strong in the minds of students so that they will firmly reject various forms of corruption.